2018
DOI: 10.5144/0256-4947.2018.8
|View full text |Cite
|
Sign up to set email alerts
|

Association between the mode of transport and in-hospital medical complications in trauma patients: findings from a level-I trauma center in Saudi Arabia

Abstract: BACKGROUNDIn Saudi Arabia, injury is the leading cause of death. Even if nonfatal, the impact of injuries on population health is enormous, as thousands of young patients suffer permanent disabilities every year. Unlike in developed countries, private transportation (PT) is a common means to transport trauma patients. Outcome differences between patients transported via PT relative to emergency medical services (EMS) has not been previously explored.OBJECTIVESTo evaluate the association between transportation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…However, it is possible that patients transported by ambulances have more severe injuries than those transported via private vehicles. Approximately two thirds of all of the patients transported to the KAMC came via private transportation, which is similar to the results of a previous local study [34]. This estimate is higher than expected, and it may be explained by a lack of awareness about how to contact emergency services [35].…”
Section: Discussionsupporting
confidence: 83%
“…However, it is possible that patients transported by ambulances have more severe injuries than those transported via private vehicles. Approximately two thirds of all of the patients transported to the KAMC came via private transportation, which is similar to the results of a previous local study [34]. This estimate is higher than expected, and it may be explained by a lack of awareness about how to contact emergency services [35].…”
Section: Discussionsupporting
confidence: 83%
“… 24 25 Nonetheless, two regional studies from Riyadh and Oman reported no substantial differences in mortality among injured patients transported by EMS compared with private cars. 26 27 Several important variables should be considered, such as the severity and nature of injuries in patients delivered by EMS, the extrication time, and scene time in patients requiring immediate pre-hospital care. Thus, due to the lack of strong evidence, we are only able to speculate on the possible reasons for our finding of decreased mortality with private transportation of TBI cases, encouraging future reports to further investigate the variables associated with increased mortality among EMS transported patients.…”
Section: Discussionmentioning
confidence: 99%
“…Prehospital triasis, checking of the patient and adequate estimation of the injury type is an important factor in bringing decision about should the patient be transported into the nearest hospital or specific hospital ( 18 , 28 ).…”
Section: Discussionmentioning
confidence: 99%